The Effects Of Non-Physical Work Environment, Motivation And Compensation On Employee Turnover - Juliyanti, Julia; Rahmi , Palupi Permata (International Journal of Marketing & Human Resource Research, 2025)
This study aims to analyze the effect of non-physical work environment, motivation, and compensation on employee turnover in service companies. The research was conducted at PT Permodalan with a quantitative approach and descriptive verification method. The research sample amounted to 35 respondents who were taken with saturated sample technique. Data collection was done through a closed questionnaire using a Likert scale. The data were analyzed using multiple linear regression preceded by validity, reliability, and classical assumption tests. The results show that motivation and compensation have a significant effect on employee turnover, while the non-physical work environment has a negative effect but is not statistically significant. Simultaneously, the three independent variables have a significant effect on turnover, with a contribution of 46% to the variability of turnover (R² = 0.460). This finding confirms the important role of fair compensation and strategic management of work motivation in reducing employee turnover. The managerial implications of this study suggest that companies balance the aspects of rewards, career development, and work climate to maintain workforce loyalty on an ongoing basis.